Zastosowanie symbolicznej analizy czynnikowej do klasyfikacji obiektów symbolicznych - Wójcik, Małgorzata (Approach Symbolic Factorial Discriminant Analysis into Symbolic Objects Classification, 2005)
In the article the bases of Factorial Discriminant Analysis are introduced. The method allows to discover dependency among various symbolic objects characteristic. The main objectives are defining a geometrical classification rules and visualizing on a factorial plane the classes of symbolic objects, separated from each other in the best way. To sum up the example based on SODAS programme was introduced.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 387-395